2002
DOI: 10.1006/jecp.2002.2660
|View full text |Cite
|
Sign up to set email alerts
|

Counting in Sign Language

Abstract: Do the visuomanual modality and the structure of the sequence of numbers in sign language have an impact on the development of counting and its use by deaf children? The sequence of number signs in Belgian French Sign Language follows a base-5 rule while the number sequence in oral French follows a base-10 rule. The accuracy and use of sequence number string were investigated in hearing children varying in age from 3 years 4 months to 5 years 8 months and in deaf children varying in age from 4 years to 6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 25 publications
4
31
1
4
Order By: Relevance
“…Indeed, several imaging studies of counting showed activation in Broca's area, in the primary motor cortex in the mouth region, and right cerebellum, all associated with internal speech (Hinton and others 2004). Deaf children perform identically to hearing children on this task, using their visuospatial rehearsal loop (Leybaert and Van Cutsem 2002). Contrary to estimation and small numerosity apprehension, the counting mechanisms have no equivalent in nonhuman animals, are not universal among human cultures (Gordon 2004;Pica and others 2004), and are acquired very progressively in an effortful process by human children (Wynn 1990).…”
Section: Exact Representation Of Large Numerositymentioning
confidence: 98%
“…Indeed, several imaging studies of counting showed activation in Broca's area, in the primary motor cortex in the mouth region, and right cerebellum, all associated with internal speech (Hinton and others 2004). Deaf children perform identically to hearing children on this task, using their visuospatial rehearsal loop (Leybaert and Van Cutsem 2002). Contrary to estimation and small numerosity apprehension, the counting mechanisms have no equivalent in nonhuman animals, are not universal among human cultures (Gordon 2004;Pica and others 2004), and are acquired very progressively in an effortful process by human children (Wynn 1990).…”
Section: Exact Representation Of Large Numerositymentioning
confidence: 98%
“…Deaf children lag behind hearing children in learning to count, independently of whether they are learning to count orally or in sign (Leybaert and Van Cutsem 2002). Consequently, they perform less well than hearing children on schoolentry numeracy tests, which typically include tasks that require counting (e.g., "show me 5 blocks"; "tell me which number is bigger").…”
Section: Countingmentioning
confidence: 99%
“…These delays do not start at school age. Research indicates that even preschool-age deaf children (3-5 years) may be substantially behind in foundational mathematics concepts (Leybaert & Van Cutsem, 2002;Kritzer, 2009aKritzer, , 2009b.…”
mentioning
confidence: 99%